2018
DOI: 10.3906/sag-1707-122
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of standard agglutination tests, enzyme immunoassay, and Coombs gel test used in laboratory diagnosis of human brucellosis

Abstract: Background/aim: It was aimed to evaluate the results of Rose Bengal (RB), ELISA total tests (IgM and IgG), and the Brucella Coombs gel test (BCGT), which are used as screening tests, with the combined results of a tube agglutination test (standard Wright test: SWT) and a tube agglutination test with antihuman globulin (AHG TAT). Materials and methods:Samples from 97 patients prediagnosed with brucellosis (age ≥18 years) were screened with RB, ELISA, and BCGT. SWT < 160 samples and RB-negative but ELISA-or BCGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…A study performed in 2015 [24] reported that BCGT was in excellent agreement with the Brucella immuncapture test (K=0.979). Another study [5] stated similar findings as with others, that BCGT was in almost perfect agreement with classic coombs test (K=0.846), though Koçman et al [16] detected that the BCGT (above 1/160) was in good agreement with Brucella immuncapture test (K=0.724). In our study, we detected that there was an excellent agreement between the BCGT and BCAP tests with the following Kappa test findings: K=0.824.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…A study performed in 2015 [24] reported that BCGT was in excellent agreement with the Brucella immuncapture test (K=0.979). Another study [5] stated similar findings as with others, that BCGT was in almost perfect agreement with classic coombs test (K=0.846), though Koçman et al [16] detected that the BCGT (above 1/160) was in good agreement with Brucella immuncapture test (K=0.724). In our study, we detected that there was an excellent agreement between the BCGT and BCAP tests with the following Kappa test findings: K=0.824.…”
Section: Discussionsupporting
confidence: 67%
“…The results were closely similar; however, only a study reported [16] that the sensitivity of BCGT was 78.8%, if the titer was above 1/160, and the accuracy of this test was 88.7%. In our study, we compared the positivity results of BCGT to BCAP.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In addition to the patient's history and physical examination findings, some tests, such as the Rose Bengal test, Brucella tube agglutination test, Coombs test, and blood culturing, are required for the diagnosis of brucellosis (9). Blood culturing is the gold standard for the diagnosis of brucellosis; however, it is difficult to cultivate the bacteria owing to the long incubation period, them being biosafety level 3 organisms, antibiotic susceptibility, the culture medium, and the need for specialized and experienced personnel (10,11). In chronic cases, the culturing often fails or takes a long time.…”
Section: Discussionmentioning
confidence: 99%